FORMULATION AND ANTIOXIDANT ACTIVITY TEST OF FACE TONER EXTRACT PREPARATION FROM 70% ETHANOL OF CUCUMBER FRUIT (Cucumis sativus L.) - Safitri, Meta; Sauri, Sufyan; Kuncoro, Banu; Aprilliani, Arini (Jurnal Farmasi Sains dan Praktis, 2024)
Cucumber (Cucumis sativus L.) is a natural ingredient with potential therapeutic properties for addressing various skin-related problems. The study aims to identify a suitable formulation for a facial toner extract that exhibits favourable physical properties as determined by organoleptic, homogeneity, pH, and hedonic testing. The present study employed an experimental approach to produce a 70% ethanol extract of cucumber fruit through the maceration method, utilising 70% ethanol solvent. Subsequently, the extract derived from the cucumber fruit developed four formulas to prepare face toners. The concentrations of these formulas were designated as F0 (0%), FI (0.5%), F2 (1%), F3 (1.5%), and F4 (utilising brand x toner as a positive control). The physical evaluation test yielded the fulfilment of the physical criteria for the toner, encompassing the organoleptic, homogeneous, pH, and hedonic tests. The IC50 values obtained from the antioxidant activity test conducted on face toner preparations containing cucumber fruit extract at concentrations of 0.5%, 1%, and 1.5% were found to be 128 ppm, 91.017 ppm, and 62.218 ppm, respectively. The SPSS analysis reveals a significant difference in the IC50 value among the various formulas. Specifically, F3 exhibits a smaller IC50 value than the other formulas, indicating a stronger antioxidant activity. It is important to note that a smaller IC50 value indicates a stronger antioxidant activity. The study's findings suggest a positive correlation existing between the extract's concentration and its antioxidant activity, specifically, the extract denoted as F and administered at a concentration of 1.5%.